Interactive E-book for Physics Learning: Analysis of Students’ Characters and Conceptual Understanding - Septikasari, Anisa Nur; Maison, Maison; Nazarudin, Nazarudin (Indonesian Journal of Science and Mathematics Education, 2021)
The national education curriculum is concerned with character building. The development of media with character needs to be done to strengthen character and to help students understand the momentum and impulses concept. This study aims to (1) develop an interactive e-book and (2) describe the character and understanding of students’ concepts after using the e-book. The development model used Lee and Owens with the stages: analysis, design, development and implementation, and evaluation. An interactive e-book was prepared by combining character values in the content, discussion sheets, and online evaluation. The e-book product contains images, videos, text input functionality and can be accessed via a smartphone. Students can study matter, momentum, and impulses without the basis of space and time. The results of the study state: (1) interactive e-books are feasible and easy to use by students (2) e-books that provide character reinforcement and are effective in increasing understanding of concepts in 10% low categories to 60% high categories